Allocation of rhodamine-loaded nanocapsules from blood circulatory system to adjacent tissues assessed in vivo by fluorescence spectroscopy. (21st August 2018) - Tarakanchikova, Yana; Stelmashchuk, Olga; Seryogina, Evgeniya; Piavchenko, Gennadii; Zherebtsov, Evgeny; Dunaev, Andrey; Popov, Alexey; Meglinski, Igor
Abstract: Modern fluorescent modalities play an important role in the functional diagnostic of various physiological processes in living tissues. Utilizing the fluorescence spectroscopy approach we observe the circulation of fluorescent-labelled nanocapsules with rhodamine tetramethylrhodamine in a microcirculatory blood system. The measurements were conducted transcutaneously on the surface of healthy Wistar rat thighs in vivo . The administration of the preparation capsule suspension with a rhodamine concentration of 5 mg kg −1 of the animal weight resulted in a two-fold increase of fluorescence intensity relative to the baseline level. The dissemination of nanocapsules in the adjacent tissues via the circulatory system was observed and assessed quantitatively. The approach can be used for the transdermal assessment of rhodamine-loaded capsules in vivo .